Redesigning the Boundaries of Corruption in Government Procurement of Goods and Services - Andi Akbar Subari; Achmad Faisal; Suprapto Suprapto (International Journal of Sociology and Law, 2025)
Government procurement, particularly in Indonesia, remains highly susceptible to corruption due to systemic regulatory loopholes and excessive human discretion, often characterized by collusion and bid-rigging. This institutional vulnerability defines the traditional "boundaries of corruption" as the discretionary corridors within existing administrative law. This research aims to fundamentally redesign these boundaries by shifting control from human discretion to technological enforcement. This study employs normative legal research focusing on the Presidential Regulation on Procurement, integrated with a technological design approach relevant to the journal. The core contribution is a reform model proposing the mandatory integration of AI-powered Smart Contracts and Distributed Ledger Technology (Blockchain) into the public procurement process. Key findings indicate that the primary corrupt boundary lies in ambiguous clauses concerning direct appointments and contract amendments. We propose that an AI-based system can monitor real-time pricing anomalies and bidder networks (network analysis), while Smart Contracts can automate and audit execution, thereby eliminating human factor vulnerability. This redesign transforms the boundaries of corruption from a matter of criminal enforcement to one of algorithmic inevitability, providing a robust, transparent, and self-auditing framework for digital governance.